Reading - Davis, Philip (Philip Maurice); Magee, Fiona (Bingley, U.K. : Emerald Publishing Limited, 2020)
Can reading literature really help our mental health? This book shows how and why - not by instruction or prescription but by emotion and exploration. Offering case histories of individual readers and reading groups based on the work of The Reader, a charity dedicated to bringing serious literature to neglected communities, the authors showcase how a whole new demographic might get into reading, and in doing so unlock the emotional intelligence and benefits to health and wellbeing which come from our access to written human stories and imagined situations.
Intro -- Half Title Page -- ARTS FOR HEALTH -- Copyright Page -- Title Page -- Contents -- Series Preface: Creative Public Health -- Introductory Note -- 1: Why Reading? -- Notes -- 2: What Helps? -- Quantitative Measures, Self-reporting Questionnaires, and Interviews -- Language Analysis -- Physiological Measures -- Conclusion: The Whole Thing -- Notes -- 3: Who Can Benefit? -- Some Children -- Some Adults -- Older Adults -- Notes -- 4: How to Engage with Reading? -- Section 1: What Is Engaged Reading? -- Section 2: How to Do This Kind of Engaged Reading? -- Things To Do -- On My Own -- Things to do on my own (1): Try the reading app -- Things to do on my own (2): Making notes or writing a reading diary -- Things to Do -- With Others -- Things to Do -- for Others -- Things to See and Hear -- Notes -- 5: What Can Professionals Do to Help? -- Against 'Professionalism' -- In Favour of the Practical -- Starting Up -- Getting In -- Staying In -- Breaking Through -- It's Not Over -- Contexts for the Delivery of Shared Reading -- Family Home -- Care Homes -- Health Care Settings -- Prisons and Secure Settings -- Notes -- 6: What are the Challenges and How to Overcome Them? -- Public and Social Challenges You Face -- Further Professional and Practical Challenges -- The Challenge of Choice: Who Chooses What? -- The Challenge of Resistance -- 1. Arthur -- 2. Mark -- 3. Heather -- Notes -- 7: Useful Links and Further Reading -- Links -- Suggested Further Reading -- Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Books and reading; Language Arts & Disciplines, Reading Skills; Reading skills